Letter from Campbell Morfit to Joseph Henry, February 18, 1851 - Morfit, Campbell (1851)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Joseph Henry (1797-1878), Secretary of the Smithsonian Institute, informing him that the Smithsonian Institute has declined to publish a report; in any exchange of letters, Henry upbraids Morfit for contacting him in Booth's stead.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Chemists; Henry, Joseph, 1797-1878; Science publishing